Vascular flora and vegetation of Parinacochas lake and neighborhoods (Ayacucho, Peru) - Roque, José E. (2008)
Parinacochas lake, located in the southernmost part of the department of Ayacucho, to 3200 m of altitude, is considered as an important high-Andean wetland; however, its floristic richness is little known. As an attempt to cover this empty of botanical information, results of evaluations made between years 2003 and 2006 in this high-Andean ecosystem are presented. The vascular flora is represented by 234 taxa (225 species and nine infraspecific taxa), in 179 genera and 73 families; Asteraceae, Poaceae and Fabaceae are families with the largest number of species. Seven vegetation types are found, being shrublands the most diverse. Twenty taxa, including five subspecies, are considered endemics to the country; likewise, knowledge about departmental distribution of 93 taxa is increased. Cattle constitutes the main anthropic threat, while other human activities do not put at risk the wild flora and vegetation of this ecosystem.